Elimination of Toxic Microsatellite Repeat Expansion RNA by RNA-Targeting Cas9 - Batra, Ranjan (Cell, 2017)
Microsatellite repeat expansions in DNA produce pathogenic RNA species that cause dominantly inherited diseases such as myotonic dystrophy type 1 and 2 (DM1/2), Huntington’s disease, and C9orf72-linked amyotrophic lateral sclerosis (C9-ALS). Means to target these repetitive RNAs are required for diagnostic and therapeutic purposes. Here, we describe the development of a programmable CRISPR system capable of specifically visualizing and eliminating these toxic RNAs. We observe specific targeting and efficient elimination of micro-satellite repeat expansion RNAs both when exogenously expressed and in patient cells. Importantly, RNA-targeting Cas9 (RCas9) reverses hallmark features of disease including elimination of RNA foci among all conditions studied (DM1, DM2, C9-ALS, polyglutamine diseases), reduction of polyglutamine protein products, relocalization of repeat-bound proteins to resemble healthy controls, and efficient reversal of DM1-associated splicing abnormalities in patient myotubes. Finally, we report a truncated RCas9 system compatible with adeno-associated viral packaging. This effort highlights the potential of RCas9 for human therapeutics.